Fracture Toughness and Charpy CVN Data for A36 Steel with Wet Welding - Méndez,Gerardo Terán (2017)
Abstract This study presents KIC data obtained from KIC-CVN correlations from Charpy CVN values. For this study, T-welded connections were manufactured from ASTM A36 and E6013 electrodes in dry conditions. Then, a rectangular grinding at the weld toe was carried out and filled with wet welding. Charpy specimens were extracted to obtain CVN values. An exhaustive search through the literature of several authors was performed to collect experimental CVN data about wet welding being applied to A36 steel for comparison with CVN data obtained in this study. By using Charpy impact energy (CVN), KIC values could be predicted by KIC-CVN correlations. In addition, correlations were presented to obtain KIC values in the lower shelf, transition temperature zones and different zones for the energy-temperature curve of A36 steel. Of these correlations, Barsom’s equation was adopted, because he applied the stress yield (σYS) of the material and it can be applied in all zones for the energy-temperature curve. The results revealed that CVN values are proportionate to KIC, this data decreases as water depth increases. This took place because several discontinuities, such as, porosity, slag inclusion, non-metallic inclusion, cracking and microstructures are present in the wet welding.